Breaking the limitation of mode building time in an optoelectronic oscillator - Tengfei Hao (Nature Portfolio, 2018)
In optoelectronic oscillators used to produce chirps for radar or communications, low phase noise usually comes at a cost of slow tuning due to mode-building time. The authors use Fourier-domain mode locking to break this limitation and enable fast-tunable chirp production for microwave photonics.